MiR-1207 overexpression promotes cancer stem cell–like traits in ovarian cancer by activating the Wnt/β-catenin signaling pathway - Wu, Geyan (Oncotarget, 2015)
Wnt/β-catenin signaling pathway is strictly controlled by multiple negative regulators. However, how tumor cells override the negative regulatory effects to maintain constitutive activation of Wnt/β-catenin signaling, which is commonly observed in various cancers, remains puzzling. In current study, we reported that overexpression of miR-1207 in ovarian cancer activated Wnt/β-catenin signaling by directly targeting and suppressing secreted Frizzled-related protein 1 (SFRP1), AXIN2 and inhibitor of β-catenin and TCF-4 (ICAT), which are vital negative regulators of the Wnt/β-catenin pathway. We found that the expression of miR-1207 was ubiquitously upregulated in both ovarian cancer tissues and cells, which inversely correlated with patient overall survival. Furthermore, overexpression of miR-1207 enhanced, while silencing miR-1207 reduced, stem cell-like traits of ovarian cancer cells in vitro and in vivo, including tumor sphere formation capability and proportion of SP+ and CD133+ cells. Importantly, upregulating miR-1207 promoted, while silencing miR-1207 inhibited, the tumorigenicity of ovarian cancer cells. Hence, our results suggest that miR-1207 plays a vital role in promoting the cancer stem cell-like phenotype in ovarian cancer and might represent a potential target for anti-ovarian cancer therapy.